Demand‐oriented performance assessment using models of different degree of complexity. (27th January 2022) - Bertero, Agustin; Bertero, Raúl D.; Filippou, Filip C.
Abstract: This paper presents a procedure for evaluating performance objectives expressed in terms of the intended exceedance rate of a certain level of seismic demand. With the purpose of keeping the computational effort at a manageable level, the procedure relies on the use of structural models of different degree of complexity: a simplified predictor model that allows conducting hundreds of response history analyzes in a small computational time, and a sophisticated reference model able to realistically simulate overall system response. The former is used for the purposes of identifying a reduced set of ground motions for evaluating the performance objective of interest, which are then used as the input motions in the latter to estimate the level of demand with the specified exceedance rate and obtain additional insight into understanding the system in case performance needs to be improved. By introducing an intermediate structure‐specific predictor model, the so‐called demand‐oriented assessment is able to provide results that are more accurate than those obtained from intensity‐based assessments, while significantly reducing the computational effort associated to rigorous probabilistic seismic demand analysis.